An experimental study of the scatter correction by using a beam-stop-array algorithm with digital breast tomosynthesis - Kim, Ye-seul; Park, Hye-Suk; Kim, Hee-Joung; Choi, Young-Wook; Choi, Jae-Gu (Journal of the Korean Physical Society, 2014)
Digital breast tomosynthesis (DBT) is a technique that was developed to overcome the limitations of conventional digital mammography by reconstructing slices through the breast from projections acquired at different angles. In developing and optimizing DBT, The x-ray scatter reduction technique remains a significant challenge due to projection geometry and radiation dose limitations. The most common approach to scatter reduction is a beam-stop-array (BSA) algorithm; however, this method raises concerns regarding the additional exposure involved in acquiring the scatter distribution. The compressed breast is roughly symmetric, and the scatter profiles from projections acquired at axially opposite angles are similar to mirror images. The purpose of this study was to apply the BSA algorithm with only two scans with a beam stop array, which estimates the scatter distribution with minimum additional exposure. The results of the scatter correction with angular interpolation were comparable to those of the scatter correction with all scatter distributions at each angle. The exposure increase was less than 13%. This study demonstrated the influence of the scatter correction obtained by using the BSA algorithm with minimum exposure, which indicates its potential for practical applications.